Pembubaran HTI Ditinjau menurut PERPPU No. 2 Tahun 2017 Tentang Ormas - Muhammad Yasid Nasution; Dermina Dalimunthe (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This study examines how to dissolve HTI organizations. The type of this research is normative research with a law approach, while the primary data source is Law no. 17 of 2013 concerning Community Organizations, PERPPU No. 2 of 2017 concerning Community Organizations and secondary data from books, journals and documents related to this research, the data collection technique is by tracing and documenting, while the data analysis technique uses inventory, identification, classification and systematization. The results of this study that the dissolution of HTI did not go through the procedures based on Law no. 17 of 2013 because Law No. 17 of 2013 concerning Ormas cannot explicitly and quickly deal with HTI which in the government's view has opposed Pancasila and HTI is trying to change the state ideology into the ideology of caliphate and this threatens the integrity of the Unitary Republic of Indonesia. If the government dissolves HTI with the procedure of Law no. 17 of 2013 it will take a long time because it must go through a judicial process first. The issuance of PERPPU No. 2 of 2017 concerning Ormas even though there is still Law no. 17 of 2013 because the government saw a threat from mass organizations that spread an ideology that was contrary to Pancasila.